Retrograde transport of gamma-amino[3H]butyric acid reveals specific interlaminar connections in the striate cortex of monkey. - Somogyi, P; Cowey, A; Kisvárday, Z; Freund, T; Szentágothai, J (1983)
Several lines of evidence suggest that gamma-aminobutyric acid is an inhibitory neurotransmitter in the cerebral cortex. To study the intracortical projection of neurons that selectively accumulate this amino acid, we injected radioactive gamma-aminobutyric acid into the upper layers of the striate cortex of monkeys along tracks at an oblique angle to the pia. Sections from the injected area were then processed by a combination of autoradiography and Golgi impregnation to reveal the distribution of labeled neurons and their morphological characteristics. Labeled neurons always occurred around the injection site in each layer. In addition, a consistent radial pattern of perikaryal labeling was observed in layers IVc-VI below the injection track in layers I-IVa. The closer the injection track was to the pia the deeper the peak density of labeled cells appeared. After injection in layers IVa and the lower part of III, the highest number of labeled neurons was in layer IVc; after injection in the upper part of layer III, most labeled neurons were in layer V; and, after injection in layers I and II, the proportion of labeled neurons increased in the lower part of layer V and in layer VI. All these neurons in the infragranular layers are presumably labeled by retrograde axonal transport via the labeled fiber bundles that extended from upper to lower layers. Thirty-four Golgi-stained neurons of various types were also examined for retrograde labeling. Two were labeled, and both were aspiny stellate cells in layer V. The arrangement of these putative GABAergic neurones, with axons that ascend from lower to upper layers in a regular pattern and arborize locally, would enable them to mediate inhibition within cortical columns and between neighboring columns.